Transcriptome analysis of wheat inoculated with Fusarium graminearum - Erayman, Mustafa; Turktas, Mine; Akdogan, Guray; Gurkok, Tugba; Inal, Behcet; Ishakoglu, Emre; Ilhan, Emre; Unver, Turgay (Frontiers in Plant Science, 2015)
Plants are frequently exposed to microorganisms like fungi, bacteria, and viruses that cause biotic stresses. Fusarium head blight (FHB) is an economically risky wheat disease, which occurs upon Fusarium graminearum (Fg) infection. Moderately susceptible (cv. “Mizrak 98”) and susceptible (cv. “Gun 91”) winter type bread wheat cultivars were subjected to transcriptional profiling after exposure to Fg infection. To examine the early response to the pathogen in wheat, we measured gene expression alterations in mock and pathogen inoculated root crown of moderately susceptible (MS) and susceptible cultivars at 12 hours after inoculation (hai) using 12X135K microarray chip. The transcriptome analyses revealed that out of 39,179 transcripts, 3668 genes in microarray were significantly regulated at least in one time comparison. The majority of differentially regulated transcripts were associated with disease response and the gene expression mechanism. When the cultivars were compared, a number of transcripts and expression alterations varied within the cultivars. Especially membrane related transcripts were detected as differentially expressed. Moreover, diverse transcription factors showed significant fold change values among the cultivars. This study presented new insights to understand the early response of selected cultivars to the Fg at 12 hai. Through the KEGG analysis, we observed that the most altered transcripts were associated with starch and sucrose metabolism and gluconeogenesis pathways.